Phonemic awareness and word reading in English and Filipino of first graders - Laudiano, Raidis E. (2006)
This study investigated the relationships that existed between phonemic awareness and word reading in the subjects'first language and second language, and the possible cross-language relationship between the two languages under study. The participants were 45 Grade One students in the Puerto Princesa Pilot Elementary School in Palawan. They were given a battery of tests that measured phonemic awareness in English and Filipino, and word reading in English and Filipino. The study was able to confirm the theory of reciprocal causation, interdependency hypotheses, and theory of common underlying proficiency.
"October 2006."
Thesis (M.A. Education : Reading Education)--University of the Philippines, Diliman.
Keywords: Reading (Elementary) -- Philippines -- Puerto Princesa (Palawan).; Reading -- Phonetic method -- Philippines -- Puerto Princesa (Palawan).; Word recognition; English language -- Study and teaching (Elementary) -- Philippines -- Puerto Princesa (Palawan).; Filipino language -- Study and teaching (Elementary) -- Philippines -- Puerto Princesa (Palawan).